2021
DOI: 10.1051/0004-6361/202039409
|View full text |Cite
|
Sign up to set email alerts
|

Location and energetics of the ultra-fast outflow in PG 1448+273

Abstract: Context. Ultra-fast outflows (UFOs) are the most powerful disk-driven winds in active galactic nuclei (AGNs). Theoretical and observational evidence shows that UFOs play a key role in the AGN feedback mechanism. The mechanical power of the strongest UFOs may be enough to propagate the feedback to the host galaxies and ultimately shape the AGN-galaxy coevolution. It is therefore of paramount importance to fully characterize UFOs, their location, and energetics. Aims. We study two XMM-Newton archival observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 76 publications
(99 reference statements)
4
25
0
Order By: Relevance
“…High-λ Edd AGN are also likely to accelerate powerful outflows, which can provide an additional effect contributing to weaken the X-ray emission. Laurenti et al (2021) analysed the UFO in the NLSy1 galaxy PG 1448+273 with λ Edd ∼ 0.75. They found that this source underwent large variations in α ox , with a maximum offset of ∆α ox = −0.7, after the UFO was detected.…”
Section: Properties Of the X-ray Continuum And X-ray Weaknessmentioning
confidence: 99%
See 1 more Smart Citation
“…High-λ Edd AGN are also likely to accelerate powerful outflows, which can provide an additional effect contributing to weaken the X-ray emission. Laurenti et al (2021) analysed the UFO in the NLSy1 galaxy PG 1448+273 with λ Edd ∼ 0.75. They found that this source underwent large variations in α ox , with a maximum offset of ∆α ox = −0.7, after the UFO was detected.…”
Section: Properties Of the X-ray Continuum And X-ray Weaknessmentioning
confidence: 99%
“…Accordingly, the AGN feedback mechanism should manifest itself in full force in high-λ Edd sources, making them the ideal laboratory for probing the real impact of nuclear activity on the evolution of massive galaxies (e.g. Reeves et al 2009;Nardini et al 2015;Tombesi et al 2015;Marziani et al 2016;Bischetti et al 2017Bischetti et al , 2019Laurenti et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, r, t are in units of the gravitational radius and time, r G = GM c 2 , t G = r G c respectively, and v is in units of c. We span the interval between 5 and 500 r G for r 0 , to encompass the typical launching radius of UFOs, which usually lies between ∼50 and some hundreds of r G (Tombesi et al 2012(Tombesi et al , 2013(Tombesi et al , 2015Nardini et al 2015;Laurenti et al 2021). We divide this interval in five logarithmically spaced steps: r 0 ∈ [5.…”
Section: One-dimensional Spherically Symmetric Wind Modelmentioning
confidence: 99%
“…Fast outflows, particularly ultra-fast outflows (UFOs), are routinely observed in active galactic nuclei (AGN) as blueshifted absorption and emission features imprinted on the X-ray spectrum, with velocities ranging from ∼0.03 to 0.4−0.5 times the speed of light, c (Tombesi et al 2011(Tombesi et al , 2015Nardini et al 2015;Fiore et al 2017;Parker et al 2017;Laha et al 2020). They are launched at accretion disc scales from the central supermassive black hole (SMBH) and may display a kinetic power as high as 20−40% of the bolometric luminosity of the AGN (Feruglio et al 2015;Nardini et al 2015;Nardini & Zubovas 2018;Laurenti et al 2021), which is more than enough to trigger a massive feedback in the host galaxy, according to theoretical models (Di Matteo et al 2005;Hopkins & Elvis 2010;Gaspari et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…High-λ Edd AGN are also likely to accelerate powerful outflows, which can provide an additional effect contributing to weaken the X-ray emission. Laurenti et al (2021) analysed the UFO in the NLSy1 galaxy PG 1448+273 with λ Edd ∼ 0.75. They found that this source underwent large variations of α ox , with a maximum offset of ∆α ox = −0.7, after the UFO was detected.…”
Section: Properties Of the X-ray Continuum And X-ray Weaknessmentioning
confidence: 99%

X-ray spectroscopic survey of highly-accreting AGN

Laurenti,
Piconcelli,
Zappacosta
et al. 2021
Preprint
Self Cite